Psychological Intimate Partner Violence, Insecure Attachment, and Parental Psychological Control from Adolescence to Emerging Adulthood - Choe, So Young (Journal of interpersonal violence, 2022)
We examine if psychological intimate partner violence (pIPV) is predicted by parental psychological control (PPC) via insecure attachment. Our results analyzing longitudinal data from the Child Development Project show that PPC perceived at age 16 predicts insecure attachment at age 18, which then predicts pIPV at age 24. Moreover, the paths with attachment anxiety are consistently significant while ones with attachment avoidance are not. Further, all the paths are significant regardless of the gender of the adolescents and parents, which indicates that PPC is detrimental regardless of the gender of the adolescents or parents. Lastly, PPC perceived at age 16 does not directly predict pIPV at age 24, which suggests that social learning theory of aggression (Bandura, 1978) may not explain the association from PPC to pIPV. Our results suggest that research and practice would benefit by considering PPC as an antecedent of pIPV via insecure attachment from adolescence to emerging adulthood.